Предмет: Алгебра, автор: kaspiskdag

Помогите пожалуйста решить

Приложения:

Ответы

Автор ответа: iriska124
0
1)х1+х2=46
х1²+х2²=1156
так как
х1=46-х2
(46-х2)²-х2²=1156
2116-92х2+х2²-х2²=1156
-92х2=1156-2116
-92х2=-960
х2=96092=24023
тогда
х1=46-24023=46*23-24023=81823
Ответ --- (81823, 24023)
2)н1*н2=273
н1-н2=8
н1=8+н2
то есть
н2*(8+н2)=273
8н2+н2²-273=0
н2²+8н2-273=0
Д=64-4*(+1)*(-273)=64+1029=1156=34²
н21=-8-342=-21
н22=-8+342=13
то есть
н11=8+н2=8+(-21)=-13
н12=8+н2=8+13=21
Ответ ------- (-13,-21) и (21,13)
3)х²-5х-6х²-8х+12=(х+1)*(х-6)(х-2)*(х-6)=х+1х-2
а)х²-5х-6=0
Д=25-4*(-6)=25+24=49=7²
х1=5-72=-1
х2=5+72=6
б)х²-8х+12=0
Д=64-4*12=64-48=16=4²
х1=8-42=42=2
х2=8+42=122=6
Ответ ----- (х+1х-2)
4)3х²+5х-2х²-3х-10=(х+2)*(х-13)(х+2)*(х-5)=(х-13)х-5
а)3х²+5х-2=0
Д=25-4*3*(-2)=25+24=49=7²
х1=-5-76=-126=-2
х2=-5+76=26=13
б)х²-3х-10=0
Д=9-4*1*(-10)=49=7²
х1=3-72=-42=-2
х2=3+72=102=5
Ответ ----- (х-13(х-5))
5)2х²+11х-6х³+3х²-18х=(х+6)*(х-12)х*(х+6)*(х-3)=х-12(х*(х-3))
а)2х²+11х-6=0
Д=121-4*2*(-6)=121+48169=13²
х1=-11-134=-244=-6
х2=-11+134=24=12
б)х³+3х²-18х=0
х*(х²+3х-18)=0
х=0
или
х²+3х-18=0
Д=9-4*(-18)=81=9²
х1=-3-92=-122=-6
х2=-3+92=62=3
Ответ ------ (х-12(х*(х-3))
6)х³-5х²-14хх²-2х-8=х*(х-7)*(х+2)(х-4)*(х+2)=х*(х-7)х-4)
а)х³-5х²-14х=0
х*(х²-5х-14)=0
х=0
или
х²-5х-14=0
Д=25-4*(-14)=81=9²
х1=5-92=-42=-2
х2=5+92=142=7
б)х²-2х-8=0
Д=4-4*(-8)4+32=36=6²
х1=2-62=-42=-2
х2=2+62=82=4
Ответ ----- (х*(х-7)(х-4))
Похожие вопросы